PRODUCT PROMOTION STRATEGY IN SPORTS INDUSTRY - Alla V. Nosova; Mikhail S. Nosov (Статистика и экономика)
Sports industry is presented like the partof entertainment industry. The authorsemphasize the main income items ofSnowsports unions in Russia and abroad.This paper presents the analysis of development of commercial successful productby foreign federations. The article gives new ways of raising the attractiveness and proﬁtability of the Russian sport.